Museums without walls: the Salvadoran experience of cultural mediation with teaching bags (Cadernos de Sociomuseologia, 2025)
This article analyzes the university experience of cultural mediation developed through the De aquí para allá (From Here to There) project, implemented by the Research Department of the University Museum of Anthropology (MUA) at the Technological University of El Salvador. The project originally arose from the need to assess the effectiveness of museum communication and was transformed in response to the weak link between the museum and its university community. It is based on the principles of social museology and the concept of a “museum without walls.” Using a sequential explanatory design (DEXPLIS), which combined surveys, focus groups, and workshops, the perceptions and needs of the student community were identified, leading to the co-creation of an educational suitcase as a mobile and participatory teaching resource. This tool integrates content related to Salvadoran cultural heritage in different ways, promoting cultural appropriation from everyday life. The experience shows that the museum's openness to active collaboration with its community not only promotes access and inclusion, but also enriches museum narratives, enhancing their social and educational relevance.Keywords: museum without borders, cultural mediation, educational kit, cultural heritage